The Analysis of Determinant Factors Affecting The Job Performance of Islamic Bank Employees in Indonesia - Diana; Luqman Hakim; Mitsalina Tantri; Muhammad Fahmi (IJHCM (International Journal of Human Capital Management), 2022)
Public sector challenges tend to be translated into more complex job demands which require individual innovation. To deal with the demands, many public organizations implement employee performance management. The current study analyzes the key determinants of employee performance to find a new model as a reference for Islamic banking practitioners, especially in Indonesia. Data were collected by using a questionnaire, developed with Google Forms and disseminated via online social media. It employed accidental sampling technique upon 7 Islamic banks in Indonesia, by distributing questionnaires that followed a six-point Likert scale. Questionnaires were distributed to 356 employees through representatives of Islamic Banks, WhatsApp Group and LinkedIn, by which 350 respondents submitted. Thereupon, the data were tested using Structural Equation Modeling (SEM) Amos 25.0, which resulted in the finding that Work Motivation did not affect Employee Performance, and training also did not affect Employee performance. However, training significantly and positively affected cohesion with the highest path, and cohesion also affected employee performance. This study found that the main effect of employee performance is cohesion, which affirmed the research results of Appelbaum et al. (2020), Williams et al. (2016), and Kearnes (2020). The weakness of this study lied in the sample population which might be inhomogeneous because the research subjects have different organizational cultures. The study results served as a reference model for Islamic Banking directors in improving employee and banking performance, so they concern on the training factor without ignorance over the cohesion factor.